THE OXIDATIVE DISSOLUTION MECHANISM OF URANIUM DIOXIDE. I. THE EFFECT OF TEMPERATURE IN HYDROGEN CARBONATE MEDIUM - 1. EXPERIMENTAL KINETICS - Pablo J.D.; Casas I.; Gimenez J.; Molera M.; Rovira M.; Duro L.; Bruno J. (My University, 1999)
The oxidative dissolution of uranium (IV) dioxide has been experimentally investigated as a function of hydrogen carbonate concentration at 4 different temperatures (10, 25, 45, and 60°C) by using a continuous thin-layer flow-through reactor. The experimental results have been interpreted as evidence for a bicarbonate-promoted oxidative dissolution mechanism which can be differentiated in to 3 steps: 1) initial oxidation of the uranium dioxide solid surface; 2) binding of HCO3- at the U(VI) sites of the oxidized layer; and 3) detachment of the U(VI)-carbonato surface complex.From this mechanism a general rate equation has been derived: r=k1k2{>UO2}tot[O2][HCO3-]k-1+k2[HCO3-]+k1[O2]Which allows to rationalization of some of the discrepancies found in the literature concerning the dependence of the dissolution rate of uranium dioxide on the hydrogen carbonate concentration. The application of this bicarbonate-promoted oxidative dissolution mechanism allows us to predict unirradiated UO2 and spent nuclear fuel dissolution rates which are in satisfactory agreement with rates determined experimentally. Some differences observed in spent fuel dissolution rates have been attributed to radiolysis effects.